GADAI SYARIAH DALAM PERSPEKTIF EKONOMI ISLAM - Effendi, Arif (Wahana Akademika: Jurnal Studi Islam dan Sosial, 2013)
AbsractThe word mortgage is a French Law term meaning "death contract", meaning that the pledge ends or dies when either the obligation is fulfilled or the property is taken through foreclosure. A mortgage is a way to use ones real property, like motorcycle, car or gold etc. as a guarantee for a loan to get money. In Islamic economic perspective it is called Rahn.In a rahn, there is a debtor and a creditor. The debtor or rahin is the owner of the property, while the creditor or murtahin is the owner of the loan. When the rahn transaction is made, the rahn gets the money with the loan, and promises to pay the loan. The murtahin will receive money back with management fee for entrustment cost, concervancy cost, and custody cost as well as appraisal cost. If the rahin does not pay the loan, the murtahin can take and sell the mortgaged property through foreclosure.This paper will see Rahn in Islamic fiqh through Al Qurâan, As-Sunnah, Ijmaâ, and positive law of Indonesia and take an example at PT Pegadaian (Persero).Keywords: Rahn, The debtor (rahin), The creditor (murtahin)